Obtaining of nanoparticles of Sc, Ti, V, Cr, Mn, Fe, Co, Ni with controlled sizes and properties using laser ablation. (November 2019) - Simakin, Andrey; Baimler, Ingrid; Uvarov, Oleg; Rud', Ivan; Krasnoshekov, Viktor
Abstract: Using laser ablation, nanoparticles of Sc, Ti, V, Cr, Mn, Fe, Co, Ni with controlled sizes and properties were obtained. To obtain nanoparticles of a given size, not only ablation of massive targets was used, but fragmentation (exposure to a mixture of micro- and nanoparticles by laser radiation). The evolution of the particle size distribution function in the process of their laser fragmentation is investigated and its key parameters determining it are established, such as the energy density of a laser beam in a medium and the peak power of laser radiation. Different schemes for introducing laser radiation into colloidal systems have been used. To obtain nanoparticles that do not contain oxide films, organic alcohols (ethanol and propanol-2) were used as the working fluid. The obtained nanoparticles met the following criteria: 1). at least 95% of the particles in the preparation have the specified diameter; 2). The shape of the nanoparticles is close to spherical; 3). The composition of the nanoparticles does not include a significant amount of impurities and oxides; 4). In most of the nanoparticles, a metal crystal lattice is observed, although under certain conditions it is possible to obtain nanoparticles, both with the outer oxide layer and entirely consisting of oxides. The stability of the obtained colloid nanoparticles was investigated. It is assumed that the solvent is saturated with molecular hydrogen to prevent oxidation of nanoparticles during storage.